ANALGESIC AND ANTI-INFLAMMATORY EVALUATION OF ETHANOLIC EXTRACT OF SEENTHIL CHURANAM (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The polyherbal formulation of Seenthil churanam is composition of whole plant extracts of Eclipta prostata, Tinospora cordifolia and the dried powder form of Earthworm used in folk medicine. The study was conducted to evaluate the scientific figures for the treatment of anti-inflammatory and analgesic activity of ethanolic extract of Seenthil churanam by acetic acid induced writhing test and eddy’s hot plate method, and carrageenan induced paw edema method. There was significant response in analgesic and inflammatory activity at high dose (400 mg/kg) compared to low dose 200 mg/kg against the standards Analgin (500 mg/kg), Aspirin (100 mg/kg) and Diclofenac sodium (100 mg/kg) body weight of mice and rats. The results of this study show that the chronic oral administration of an ethanolic extract of Seenthil churanam at a 400 mg/kg body weight dosage be a good alternative natural medicine for analgesics and anti-inflammatory drug without side effects.